2015
DOI: 10.1155/2015/152767
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Antibiotic Susceptibility of Contact Lens Associated Microbial Keratitis

Abstract: Introduction. In recent years, the number of contact lens wearers has dramatically increased in Iran, particularly in youngsters. The purpose of current study was to assess the clinical presentation and antibiotic susceptibility of contact lens related microbial keratitis in Ahvaz, southwest of Iran. Methodology. A cross-sectional investigation of 26 patients (33 eyes) with contact lens induced corneal ulcers who were admitted to Imam Khomeini Hospital, Ahwaz City, from June 2012 to June 2013 was done. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…Also, this higher incidence of keratitis due to contact lens may be due to the tropical climate of Dubai as reported in a study in Brisbane [28]. Similarly, Pseudomonas aeruginosa was mostly isolated from tropical places with higher maximum and minimum temperatures [30], whereas lower rates are found in cooler climates [25].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Also, this higher incidence of keratitis due to contact lens may be due to the tropical climate of Dubai as reported in a study in Brisbane [28]. Similarly, Pseudomonas aeruginosa was mostly isolated from tropical places with higher maximum and minimum temperatures [30], whereas lower rates are found in cooler climates [25].…”
Section: Discussionmentioning
confidence: 69%
“…Pseudomonas aeruginosa was also found to be a major causative organism in previous studies too [24][25][26][27][28][29]. It was found that Pseudomonas aeruginosa have a tendency to adhere to the contact lens surface and it penetrates the cornea's deeper layers and leading corneal ulcers, which could cause permanent blindness [23].…”
Section: Discussionmentioning
confidence: 95%
“…In our study statistical significant ( p  < 0.05) was established between corneal ulcer and trauma (28.9%) as indicated by the culture positivity. Use of contact lenses has become one of the main reasons for microbial keratitis in the developed nations where they are broadly accessible, mainly in young adults [9, 26, 27]. In contrast to the reports cited above even a single case of corneal ulcer predisposed by contact lens wear was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance was relatively uncommon and did not increase over 12 years (from 2002 to 2013) [35]. Data from Iran suggest that Pseudomonas isolates were mostly sensitive to ciprofloxacin followed by imipenem, meropenem and ceftazidime [4]. In Canada an increasing resistance to erythromycin (p=0.018), ceftazidime (P=0.046), piperacillin/tazobactam (P=0.005) was seen in the past 16 years [21].…”
Section: Management Of P Aeruginosa Keratitismentioning
confidence: 95%
“…In Saudi Arabia, an incidence of 38.4% was reported [3].On the other hand, it has been reported that up to 80% of all positive cultures in Iran are caused by Pseudomonas spp. [4]. Moreover, P. aeruginosa was the most frequent bacteria isolated in contact Lens related ulcers with an incidence of 75% in France [5] and 79.7% in Malaysia [7].…”
Section: Epidemiology P Aeruginosa Keratitismentioning
confidence: 99%